Cylindrical and Spherical Positron-Acoustic Shock Waves in Nonthermal Electron-Positron-Ion Plasmas - M. M. Rahman (Brazilian Journal of Physics, 2015)
The nonlinear propagation of cylindrical and spherical positron-acoustic shock waves (PASWs) in an unmagnetized four-component plasma (containing nonther- mal distributed hot positrons and electrons, cold mobile viscous positron fluid, and immobile positive ions) is inves- tigated theoretically. The modified Burgers equation is derived by employing the reductive perturbation method. Analytically, the effects of cylindrical and spherical geome- tries, nonthermality of electrons and hot positrons, relative number density and temperature ratios, and cold mobile positron kinematic viscosity on the basic features (viz. polarity, amplitude, width, phase speed, etc.) of PASWs are briefly addressed. It is examined that the PASWs in nonpla- nar (cylindrical and spherical) geometry significantly differ from those in planar geometry. The relevance of our results may be useful in understanding the basic characteristics of PASWs in astrophysical and laboratory plasmas.